Characterizations of Bioflocculant Produced by Bacillus coagulans 8B and Application in Domestic Wastewater Treatment - Jwan Sabah J. Bajlan; Sanaa Burhan Alden; Osama Bassim Al-Saffar (Journal of Madenat Alelem University College, 2013)
Forty eight isolates belonged to Bacillus spp. were isolated from soil and water samples. Twenty two Bacillus isolates revealed a mucous phenotype when grown on nutrient agar plates. Only seven isolates of Bacillus were grown on starch broth media and gave flocculating activity for kaolin suspension. Isolate B8 (isolated from soil) gave the highest flocculating activity for kaolin suspension (37%). Biochemical tests for this isolate showed that B8 strain of Bacillus coagulans. The bioflocculant produced by B. coagulans B8 was extracted by organic solvents. Thin layer chromatography (TLC) analysis for B. coagulans B8 bioflocculant hydrolyzed by HCl with solvent system showed two brown spots when using phenol-sulphuric acid reagent with Rf =0.41 and 0.58 which resembled to galactose and glucose, and only one red-violet spot when using ninhydrin reagent (Rf =0.68) which may be resembled with phenylalanine. Domestic waste waters were of treated with B. coagulans B8 bioflocculant. Results showed that turbidity removal (flocculating activity) was reduced to 62.7%.